The family of Mrs. Mary Segotta (Raton Range Raton, New Mexico, 1977)
Newspaper Article on reunion of Mary Segotta and her family.
Master list item #: 14
File location is in the Raton File Cabinet
Keywords: Segotta, Mary; Williston, Mary; Segotta, Jack; Segotta, Steve; Carrolla, Antonia; Edmonson, Elizabeth; Watier, Catherine; Riali, Josephine; Trueba, Mildred; Segotta, Frank; Segotta, John; Local History; Biography; Life and Customs; Family; Reunion; Raton, New Mexico